If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1(9a + 1) + -9 = 11 + 3a Reorder the terms: -1(1 + 9a) + -9 = 11 + 3a (1 * -1 + 9a * -1) + -9 = 11 + 3a (-1 + -9a) + -9 = 11 + 3a Reorder the terms: -1 + -9 + -9a = 11 + 3a Combine like terms: -1 + -9 = -10 -10 + -9a = 11 + 3a Solving -10 + -9a = 11 + 3a Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-3a' to each side of the equation. -10 + -9a + -3a = 11 + 3a + -3a Combine like terms: -9a + -3a = -12a -10 + -12a = 11 + 3a + -3a Combine like terms: 3a + -3a = 0 -10 + -12a = 11 + 0 -10 + -12a = 11 Add '10' to each side of the equation. -10 + 10 + -12a = 11 + 10 Combine like terms: -10 + 10 = 0 0 + -12a = 11 + 10 -12a = 11 + 10 Combine like terms: 11 + 10 = 21 -12a = 21 Divide each side by '-12'. a = -1.75 Simplifying a = -1.75
| 5w+3y+4x+9y-12y+3w= | | 2x+3x+15=29 | | 3(3+3x)-5=68 | | (2x^2)*ln(sqrt(x))=0 | | 3ax=3a+3 | | 400=0.5(2x)(x) | | 2x*2y=2xy | | 47x+17= | | 20x+50y=41 | | 154=0.5(x)(19.5+24.5) | | 2x-x=16 | | 42-5x=12+10x | | 45-4x=4x^2 | | 8x-2(x+1)=6x-2 | | 10x+25y=20.50 | | sqrt(x+5)-8=1 | | 3b-14=1 | | 5y+6=4y+11 | | .6(5b-10)=(7b-4)(-2)+3 | | 3-6-4=32 | | -40+8n=2n | | -x^2+200=0 | | -10x+11x+5=-9-5 | | 11-15=6w-6-5w | | -2-3=-4+v | | U-1.2=7.5 | | 3(3f+2)=-30 | | (3t+2)+(9t^2+9t+3)= | | -3v^2+11v-6=0 | | -10=x-15 | | -12=r+4 | | (5x+35)+(4x+20)=180 |